2001
DOI: 10.1097/00000539-200110000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Labor Analgesia and Neonatal Sepsis Evaluation Rate: A Quality Improvement Study

Abstract: Although it has been suggested that epidural analgesia for labor contributes to an increase in neonatal sepsis work-up (SWU), this retrospective analysis shows that epidural analgesia is not associated with an increase in SWU. The factors that were found to contribute to SWU included low birth weight, low gestational age, meconium aspiration or respiratory distress at birth, hypothermia at birth, maternal group B beta-hemolytic colonization, and preeclampsia or hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…Guidelines for neonatal sepsis evaluation at our institution include prolonged rupture of membranes (>18 h) and chorioamnionitis; neonatal conditions include hypo-or hyperthermia at 6 h after birth, apneic spells, respiratory distress or pneumonia, central cyanosis, listlessness, convulsions, poor feeding or vomiting, and cardiovascular instability. 3 The frequency and time of epidural boluses, and the type and amount of epidural medication used were documented. Obstetric variables were number of vaginal examinations, use of oxytocin augmentation or internal monitors, time at which the membranes ruptured, whether spontaneously or artificially, group B Streptococcus colonization, and clinical suspicion of chorioamnionitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for neonatal sepsis evaluation at our institution include prolonged rupture of membranes (>18 h) and chorioamnionitis; neonatal conditions include hypo-or hyperthermia at 6 h after birth, apneic spells, respiratory distress or pneumonia, central cyanosis, listlessness, convulsions, poor feeding or vomiting, and cardiovascular instability. 3 The frequency and time of epidural boluses, and the type and amount of epidural medication used were documented. Obstetric variables were number of vaginal examinations, use of oxytocin augmentation or internal monitors, time at which the membranes ruptured, whether spontaneously or artificially, group B Streptococcus colonization, and clinical suspicion of chorioamnionitis.…”
Section: Methodsmentioning
confidence: 99%
“…2 However, a study performed at our own institution found no such association between epidural analgesia and NSE. 3 Similarly, Philip et al found that in the absence of maternal fever, epidural analgesia did not increase the NSE rate. 4 Most studies investigating maternal fever with epidural analgesia have been performed on parturients receiving continuous infusions.…”
Section: Introductionmentioning
confidence: 94%
“…[83][84][85][86] Although it is clear that maternal temperature increases in some women who receive labor epidural analgesia, the cause of the increase is controversial. 84 The mechanisms of the association between labor analgesia and maternal fever have not been fully elucidated.…”
Section: Fever: Epidural Analgesia and Maternal "Fever"mentioning
confidence: 99%
“…Similarly, Greenwell et al 26 concluded that "Among low-risk women receiving epidural analgesia, intrapartum maternal temperature >99.51F was associated with adverse neonatal outcomes," without highlighting that prolonged labor was a highly significant (P < 0.0001) predictor that offered a much more plausible explanation of the observed association. As Segal 27 noted in a recent review article, studies that make mention of maternal temperature while investigating effects of labor analgesia can be categorized as observational [28][29][30][31][32] and randomized controlled trials. [33][34][35][36][37] The common thread among those studies is that although there is a higher proportion of mothers who have Z1 temperature reading >100.41F in the epidural group, patients receiving epidural analgesia also tend to have longer labor, one of the known risk factors for chorioamnionitis.…”
Section: Epidural Analgesia and Fevermentioning
confidence: 99%